IMPLEMENTASI STRATEGI PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE+ METACOGNITIVE (TPS+M) UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN METAKOGNITIF PADA KONSEP HIDROLISIS GARAM SISWA KELAS XI-IPA 2 SMA NEGERI 4 BANJARMASIN - Krisno Kiki Susanto; Syahmani Syahmani (Universitas Lambung Mangkurat, 2012)
Has done research aims to improve learning outcomes and metacognitive skills of students as well as the response of students towards cooperative learning strategies TPS + M. This study uses a research design class action, with 2 cycles of 3 times the meeting. The research subjects were students in grade XI IPA 2-SMAN 4 Banjarmasin totaling 31 people. The data collected through the test results of study, observation, questionnaires, interviews and activity sheets. Data were analyzed by percentage and described qualitatively. The research instrument used in the form of test results to learn an instrument, questionnaire metacognitive skills, the student observation sheet questionnaire responses metacognitive skills, metacognitive activity sheet students, interview guidance sheets and teacher observation sheet activities. Results showed that learning the concept of salt hydrolysis using cooperative strategies TPS + M can improve student learning outcomes by 17.5% from 73.60% in cycle I to 91.1% in cycle II. Metacognitive skills of students through observational data increased by 15.55% with very good category and 43.34% in both categories, while through the questionnaire, students' metacognitive skills in the category increased 22.58% and 35.48% very well in either category. Graders XI IPA 2-SMAN 4 Banjarmasin responded positively to the learning concept of salt hydrolysis using cooperative learning strategies TPS+M. Keywords: Cooperative strategy TPS + M, metacognitive skills, salt hydrolysis.